Social Development Through International Relations - Gulab Mir Rahmany (UIN Sunan Gunung Djati, 2021)
With the horrific incident on September 11 in the US, the US armed forces entered Afghanistan to shut the door to terrorism. Now, Afghanistan opens a new page for Afghanistan's internal and external political system. Afghanistan as a country that has pursued regional cooperation from neighboring countries, especially from India. India is the most promising country for Afghanistan's foreign policy and diplomatic relations in areas such as economic, cultural, technical, capacity building, military and other growth. The purpose of this study is to examine the development process of the two countries India and Pakistan in an effort to establish international relations. With a qualitative approach This research resulted in India being one of the countries which, after September 11, 2001, and the leadership of the Taliban, succeeded in gaining more opportunities for the people of Afghanistan. His non-hostile contributions to Middle Eastern and Middle Eastern countries have created a special place for the people of Afghanistan. India after independence in 1947, started friendly relations with Afghanistan two years later, until now, has enthusiastically and dedicably made their contribution to Afghanistan. The people of Afghanistan in this case get many benefits from India's bilateral relations, namely the construction of the Salma Dam in Herat, Delaram Road Development, Allotment of 1000 Afghan Student Scholarships in Human Resource Development per year, the Repair of the Afghan Foreign Minister Complex, the establishment of the Afghan Parliament Building, the Opening of Chabahar Port, Strengthening the Equipment of the Afghan Military Forces, Air Corridors, and India's efforts to get Afghanistan to gain Membership in Regional Cooperation Bodies such as SAARC, BRICS, Asia Heart 'Istanbul Process'.Â